Average rate performance in the presence of correlated interferers. Issue 7 (1st April 2020) - Saluja, Deepak; Kumar, Suman
Abstract : In this work, the authors have analysed the impact of correlation among interferers, and between signal and interferers. In particular, the impact of correlation on average rate performance in an interference‐limited scenario has been studied. The user's desired channel link and interfering channel links are assumed to experience Nakagami‐ m fading. Under this assumption, they compared the average rate for the following cases: (a) interferers are independent and the user's signal‐and‐interferers are also independent, (b) interferers are correlated and the user's signal‐and‐interferers are independent, and (c) interferers are correlated and the user's signal and‐interferers are also correlated. It has been analytically shown that the average rate in case (b) is higher than the average rate in case (a) when the interferers are positively correlated. In other words, the positive correlation among the interferers increases the average rate. Furthermore, the average rate in case (c) is lower than the average rate in case (b). In other words, the positive correlation between the signal and interferers decreases the average rate. Moreover, the average rate in case (c) can be lower or higher than the average rate in case (a), depending upon the amount of correlation. Simulation results have been shown to support analytical observations.